Penerapan Teori Big Five Personality dalam Perancangan Karakter Maskot - Aryani, Tabita Nani; Ardhianto, Peter; Utami, Maya Putri (Universitas Komputer Indonesia, 2024)
The mascot, as a representative of the brand, plays a crucial role in interacting with and building relationships with the audience. In order to create a believable mascot, an understanding of the mascot's personality is necessary. This research aims to apply the Big Five Personality theory as a reference in designing mascot characters for the DKV SCU program. Primary data was collected through a questionnaire filled out by 80 respondents. Respondents were selected using purposive sampling method, consisting of DKV SCU students aged 18-23, both male and female, residing in Semarang, Central Java. The results of the research identified a series of visually recognizable characteristics related to physiological, social, and psychological aspects. Furthermore, the discussion explores the relationship between these characteristics and the five dimensions of the Big Five Personality Theory. The conclusion of this research provides recommendations regarding the concept of character related to personality in depth within the framework of the Big Five Personality Theory as a basis for mascot visual design.